LITERATURE REVIEW: ASSOCIATION BETWEEN MATERNAL SERUM ALBUMIN LEVELS AND LOW BIRTH WEIGHT (LBW)LITERATURE REVIEW: ASSOCIATION BETWEEN MATERNAL SERUM ALBUMIN LEVELS AND LOW BIRTH WEIGHT (LBW) - Stefanny Andrea Williana; Sianti Dewi; Niluh Suwasanti (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
Background: There are physiological changes during pregnancy, one of which is an increase in mother’s nutritional needs, which is protein. The most abundant plasma protein component is albumin; hypoalbuminemia is serum albumin levels below the normal values, which it can occur due to malnutrition, inflammation, kidney or liver damage where albumin is synthesized. Good nutritional status in pregnant women can prevent Low Birth Weight (LBW), while hypoalbuminemia in pregnant women can increase the risk of LBW. LBW is neonatal birth weight <2500 grams that can cause neonatal death and increase the risk of other diseases. LBW is a global problem, and in Indonesia LBW was also the most common cause of neonatal death in 2019 with a percentage of 35.3%. In Surabaya, there were 703 LBW cases (1.6%) in 2019; moreover, there were 15 LBW cases (1.92%) at Jagir Health Center in 2020. Aim: The aim of this study was to determine the association between maternal serum albumin levels and LBW. Method: The method used in this thesis is literature review with 10 research journals. The literatures that used in this literature review are journals with topics that related to the association between maternal serum albumin levels and neonatal birth weight. Result: From this literature review, there are 5 research journals conclude that there is a significant association between maternal serum albumin levels and neonatal birth weight.Conclusion: In conclusion, there is a possible association between maternal serum albumin levels and neonatal birth weight. Keywords: maternal serum albumin, hypoalbuminemia, birth weight, LBW